As raízes históricas e a consolidação política da Internacional da Educação (IE) [1912-1993] - Mello, Isabella Delcorso Cury de (2022)
The present study approaches the historical, political and social processes that developed around the constitution of the International of Education (IE), in a periodization between the years 1905 to 1993. From a theoretical point of view, the research starts from a historical-dialectical materialist understanding of capitalist society, in its stage of economic and financial globalization, with special attention to its repercussion in the world of educational work, in order to establish a critical and contextualized understanding of the origins and political conflicts that formed the first international education organizations, from the beginning of the 20th century to the moment of its consolidation, achieved in 1993, with the creation of the IE. We present in the methodological course the historical, political, economic and social context of the insertion of these organizations, bibliographic research and survey of documentary sources collected in virtual environments and libraries indicated by the International of Education office, in Brussels, Amsterdam and Bonn, as well as the of interviews with related historical characters. In conclusion, the educational historical plot permeates the political and union world of teaching organization, impossible to unlink.